In vitro differentiation of near‐unlimited numbers of functional mouse basophils using conditional Hoxb8. Issue 5 (17th April 2013) - Gurzeler, U.; Rabachini, T.; Dahinden, C. A.; Salmanidis, M.; Brumatti, G.; Ekert, P. G.; Echeverry, N.; Bachmann, D.; Simon, H. U.; Kaufmann, T.
Abstract Background Basophils constitute a rare leukocyte population known for their effector functions in inflammation and allergy, as well as more recently described immunoregulatory roles. Besides their low frequency, functional analysis of basophils is hindered by a short life span, inefficient ex vivo differentiation protocols, and lack of suitable cell models. A method to produce large quantities of basophils in vitro would facilitate basophil research and constitute a sought‐after tool for diagnostic and drug testing purposes. Methods A method is described to massively expand bone marrow–derived basophils in vitro. Myeloid progenitors are conditionally immortalized using Hoxb8 in the presence of interleukin‐3 (IL‐3) and outgrowing cell lines selected for their potential to differentiate into basophils upon shutdown of Hoxb8 expression. Results IL‐3‐dependent, conditional Hoxb8‐immortalized progenitor cell lines can be expanded and maintained in culture for prolonged periods. Upon shutdown of Hoxb8 expression, near‐unlimited numbers of mature functional basophils can be differentiated in vitro within six days. The cells are end‐differentiated and short‐lived and express basophil‐specific surface markers and proteases. Upon IgE‐ as well as C5a‐mediated activation, differentiated basophils release granule enzymes and histamine and secrete Th2‐type cytokines (IL‐4, IL‐13) and leukotriene C4. IL‐3‐deprivation induces apoptosis correlating with upregulation of the BH3‐only proteins BCL‐2‐interacting mediator of cell death (BIM) and p53 upregulated modulator of apoptosis (PUMA) and downregulation of proviral integration site for Moloney murine leukemia virus 1 kinase (PIM‐1). Conclusion A novel method is presented to generate quantitative amounts of mouse basophils in vitro, which moreover allows genetic manipulation of conditionally immortalized progenitors. This approach may represent a useful alternative method to isolating primary basophils.